Transition towards green financial sector for gaining newly perceived competitiveness by adopting a green management model - Nour Nassar; Wadim Strielkowski (Insights into Regional Development)
The purpose of the article is to outline the relationship between the green management aspects in the financial sector that lead to the green competitiveness from the external stakeholders’ perspective. The methodology used in this study is based on the Preferred Reporting Items for Systematic reviews and Meta-Analyses for Scoping Reviews (PRISMA-SCR) approach seeking to develop a greater understanding of relevant terminology, core concepts, and key factors affecting the transition process towards the green financial sector. The main outcome of this research is constructing a model of transition towards the green financial sector for gaining green competitiveness in which the external stakeholders’ perspective hass been emphasized. This study creates a research tool that can be used for weighting green managerial aspects from the external stakeholders' point of view. While performing this study, the authors were focusing on the Middle East area which constitutes the main limitation of this research. Therefore, more attention and focus on other geographical areas might be necessary for more accuracy.